Effectiveness of Cages Inducing Nasopharyngeal Dysplasia in Wistar Rats (Rattus norvegicus) - Gede Rama Hardy Nugraha; Hamsu Kadriyan; Anak Agung Ayu Niti Wedayani; Eka Arie Yuliyani (Jurnal Biologi Tropis, 2023)
The cage is a place used to put experimental animals in experimental studies to study the mechanism of the disease and its response to therapy. Formaldehyde as a carcinogenic compound can increase the occurrence of chronic inflammation which has the potential to increase the growth of cancer cells in experimental animals due to the stress experienced while in the cage. Therefore, the purpose of this study was to compare the effectiveness of large and small cages induced by formaldehyde 30 ppm against nasopharyngeal dysplasia in Wistar rats. This research is an experimental study with a true experimental design with the type of post-test only control group design. This study used 12 male Wistar rats (Rattus norvegicus) which were divided into two groups, namely the group of Wistar rats which were placed in large cages measuring (30 x 24 x 11.5) cm3 of 6 individuals, and in small cages (27 .5 x 21.5 x 9) cm3 of 6 individuals induced by 30 ppm formaldehyde with a span of 6 hours per day for 16 weeks. The rats were terminated and retro-orbital blood samples were taken to measure MDA levels and nasopharyngeal tissue to assess the degree of dysplasia. The results of this study showed that there was a statistically significant difference (p <0.05) between the degrees of nasopharyngeal dysplasia (p=0.003) and MDA levels (p=0.003) in Wistar rats in small cages and large cages. In this study the effectiveness of small cages was greater than large cages in causing dysplasia in the nasopharyngeal tissue of Wistar rats.